Validação de protótipos para auxílio no ensino de ciências para adolescentes com deficiência visual - Silva, Johny Rodrigo Yamamoto da (Universidade Federal de São Carlos, 2025)
The scarcity of accessible teaching materials compromises the educational inclusion of students with visual impairments, especially in science education in Brazil. This study aimed to validate tactile prototypes developed as assistive technology tools for teaching Chemistry to visually impaired adolescents. An action-research methodology was adopted, involving the application of the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST 2.0) questionnaire and qualitative interviews with five basic education Chemistry teachers. The results indicated high levels of satisfaction in criteria such as durability, ease of use, and effectiveness, as well as positive perceptions regarding material quality, usability, accessibility, and pedagogical relevance of the prototypes. It is concluded that the evaluated resources have the potential to promote more autonomous, sensory, and inclusive learning, benefiting both students with visual impairments and the general student population.
Validation of prototypes to help teach science to visually impaired teenagers
Keywords: Tecnologia Assistiva; Inclusão; Química; Ensino; Deficiência Visual; Usabilidade; Assistive Technology; Inclusion; Chemistry; Teaching; Visual Impairment; Usability; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO